Dimethyl fumarate modulates neutrophil extracellular trap formation in a glutathione‐ and superoxide‐dependent manner. (14th December 2017) - Hoffmann, J.H.O.; Schaekel, K.; Hartl, D.; Enk, A.H.; Hadaschik, E.N.
Summary: Background: Neutrophil (polymorphonuclear) granulocytes (PMN) have been shown to contribute to the pathogenesis of psoriasis by releasing interleukin‐17 and LL37‐DNA complexes via neutrophil extracellular traps (NETs), webs of chromatin strands decorated with antimicrobial peptides, in psoriatic skin. Fumaderm ®, a fumaric acid ester (FAE) formulation consisting of different FAE salts, has been successfully used to treat psoriasis for decades. Most recently, FAE treatment was reported to inhibit NET formation in murine epidermolysis bullosa acquisita. Objectives: To elucidate the effect of FAE treatment on human psoriasis and healthy donor NET formation. Results: Among the compounds present in the FAE formulation, dimethyl fumarate (DMF) pretreatment of human psoriasis and healthy donor PMN resulted in a consistent inhibitory effect on NET formation in response to phorbol 12‐myristate 13‐acetate but not to platelet activating factor and ionomycin. This effect was l ‐glutathione (GSH) dependent and involved a decrease in reactive oxygen species (ROS) production, a key event in NET formation. In contrast, G‐protein‐coupled signalling and protein synthesis were not involved. Monomethyl fumarate (MMF) was found to slightly reduce ROS production without affecting NET formation. Conclusions: We report DMF as a potent, stimulus‐specific, GSH‐ and ROS‐dependent modulator of NET formation. Our results support the notion that modulation of NET formation contributes to the beneficial effects of FAEs in a variety of inflammatory conditions. Abstract : What's already known about this topic? Neutrophil extracellular trap (NET) formation is a recently discovered mechanism of innate immunity that may contribute to psoriasis pathogenesis. Fumaric acid esters (FAEs) are successfully used to treat a variety of inflammatory conditions, most notably psoriasis. FAEs were shown to inhibit neutrophil function in a murine model of epidermolysis bullosa acquisita. What does this study add? Among the compounds present in the FAE formulation Fumaderm ®, only dimethyl fumarate (DMF) significantly inhibits NET formation. Inhibition of NET formation by DMF is stimulus specific and l ‐glutathione (GSH) dependent, and involves decreasing reactive oxygen species production. What is the translational message? Stimulus‐specific, GSH‐dependent inhibition of NET formation may contribute to the beneficial clinical effects of FAEs in a variety of inflammatory conditions. Respond to this article